2008
DOI: 10.1146/annurev.publhealth.29.020907.090824
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mass Communication to Change Public Behavior

Abstract: This article provides an overview of the ways in which mass communication has been used-or can be used-to promote beneficial changes in behavior among members of populations. We use an ecological perspective to examine the ways in which mass media interventions can be used to influence public behavior both directly and indirectly. Mass media interventions that seek to influence people directly-by directly targeting the people burdened by the public health problem of concern and/or the people who influence them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(194 citation statements)
references
References 79 publications
(88 reference statements)
4
172
0
7
Order By: Relevance
“…We based our plasticity estimates on empirical studies of responses to interventions at the individual and household levels aimed at changing energy consumption and related environmentally significant behaviors (12,14,21,22) and on studies of interventions to induce adoption of health-promoting behaviors that resemble energy-saving behaviors (23)(24)(25). These studies make it possible to consider how plasticity is affected by types of intervention (e.g., media campaigns, information, and financial incentives) separately and in combinations and also by the type of behavior (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We based our plasticity estimates on empirical studies of responses to interventions at the individual and household levels aimed at changing energy consumption and related environmentally significant behaviors (12,14,21,22) and on studies of interventions to induce adoption of health-promoting behaviors that resemble energy-saving behaviors (23)(24)(25). These studies make it possible to consider how plasticity is affected by types of intervention (e.g., media campaigns, information, and financial incentives) separately and in combinations and also by the type of behavior (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…The most effective interventions typically (i) combine several policy tools (e.g., information, persuasive appeals, and incentives) to address multiple barriers to behavior change; (ii) use strong social marketing, often featuring a combination of mass media appeals and participatory, community-based approaches that rely on social networks and can alter community social norms; and (iii) address multiple targets (e.g., individuals, communities, and businesses) (12,14,23,26). * Single policy tools have been notably ineffective in reducing household energy consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Several aspects make face-to-face communication more salient and effective: first, it is more personal; second, nonverbal cues can allow the communicator to gauge how the information is being received in real time and respond accordingly; direct communication also allows for dialogue to emerge; and finally, the trust between individuals participating in a two-way exchange goes a long way toward engaging and convincing someone. Interactive communication, whether face to face or over the internet, improves health outcomes and behavior change (Abroms and Maibach 2008). Not surprisingly, some have suggested employing a two-step flow in communicating climate change-from a source to an influential to the ultimate audience-to bank on the benefits of face-to-face, more direct communication (Nisbet and Kotcher 2009).…”
Section: Mobilization Through Mass Mediamentioning
confidence: 99%
“…25 Gupta and coworkers 26 reviewed policies, programmes, and transformational processes that aim to change the social, economic, political, or environ mental factors that aff ect HIV risk and vulnerability. They reported that interventions, including needle exchange programmes or condom provision to sex workers, are promising approaches to reduce susceptibility to HIV infection.…”
Section: Structural Interventions To Change Behavioursmentioning
confidence: 99%